2021
DOI: 10.3390/w13121659
|View full text |Cite
|
Sign up to set email alerts
|

Recent Changes in Hydroclimatic Patterns over Medium Niger River Basins at the Origin of the 2020 Flood in Niamey (Niger)

Abstract: Niamey, the capital of Niger, is particularly prone to floods, since it is on the banks of the Niger River, which in its middle basin has two flood peaks: one in summer (the red flood) and one in winter (the black flood). In 2020, the Niger River in Niamey reached its all-time highest levels following an abundant rainy season. On the other hand, the floods in Niamey have been particularly frequent in the last decade, a symptom of a change in hydroclimatic behaviour already observed since the end of the great d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Notably, studies have observed heightened damage and/or fatalities resulting from rare disaster events in protected areas compared to unprotected areas(Ferdous et al 2020). This trend is consistent with ndings in historical records of past disasters(Massazza et al 2021) and estimates of damage caused by extreme hydrological events in different…”
supporting
confidence: 92%
“…Notably, studies have observed heightened damage and/or fatalities resulting from rare disaster events in protected areas compared to unprotected areas(Ferdous et al 2020). This trend is consistent with ndings in historical records of past disasters(Massazza et al 2021) and estimates of damage caused by extreme hydrological events in different…”
supporting
confidence: 92%
“…In September, the highest level of the Niger river since the beginning of observations was recorded in Niamey. What happened in 2020 in Niamey is the ultimate example of a phenomena which has been growing in the last two decades in the middle Niger basin (Massazza et al 2021;Casse et al 2016). The Niger river at its middle basin experience two annual peaks: (i) The Sahelian flood-also called red flood-occurs during the rainy season, between August and September mainly from the inflows of the right bank tributaries upstream of Niamey (Gorouol, Dargol and Sirba).…”
Section: The Case Of the Recurring 'Red Floods' Phenomena In Niamey A...mentioning
confidence: 99%
“…Despite the impact of COVID-19 on the disruption of health services and on malaria cases, during the period when malaria transmission was increasing, floods have been observed in Niger, especially in Niamey and in Mali in 2019 and 2020. They were due to flooding of the Niger river [ 5 ]. This flood was itself related to a modification of the double seasonal flood of the river with an increase of the first one (August–September) associated with a change in the Sahelian climatic conditions during the last decades.…”
Section: In Sahel By the River Malaria Transmission Is Extending To T...mentioning
confidence: 99%